Cinematic Discourse Analysis: Representative Speech Acts in "Nanti Kita Cerita Tentang Hari Ini" by Marchella Febritrisia Putri - Ifa Chairin Ananda; Muhammad Yusuf Zanuar; Latifah Hannani (Ethica: International Journal of Humanities and Social Science Studies, 2024)
The investigation into representative speech acts in the film "Nanti Kita Cerita Tentang Hari Ini" forms the core idea of this research, aiming to decipher the meanings embedded in the selected film's dialogues and to understand the context and types of speech acts. A qualitative method was employed, where the researcher gathered data from the dialogues within the film "Nanti Kita Cerita Tentang Hari Ini." The data collection from this film source involved observation, note-taking, and speech act analysis, as the data comprised spoken dialogues. Representative speech acts in this context include declaring, conveying, demonstrating, agreeing, reporting, and informing. The purpose of this study is to ascertain, identify, delineate the types of representative speech acts, and analyze the forms of representative acts within the film "Nanti Kita Cerita Tentang Hari Ini." The research findings indicate a variety of representative speech acts, including 31 instances of declaring, 11 of conveying, 10 of demonstrating, 7 of agreeing, 2 of reporting, and 6 of informing.